The Potential of a Classification-based Algorithm to Calculate Calories in Real-Time Via Pattern Recognition - Mohamed Ariff, Ameedeen (2016)
Calories refer to a unit of energy that people should consume based on total energy needed. Thus, a system for health monitoring applications that can measure calories and nutrition can be very useful. This research is mainly focused on creating a new algorithm based on classification technique to calculate food calorie intake in real-time. Enhancement on Extreme Learning Machine (ELM) algorithm will be done to get better results in terms of accuracy and speed of calculating the food calorie. The ELM algorithm will be applied to an ultra-mobile Near Infrared (NIR) spectrometer. While the algorithm helped to classify different types of wavelengths produced from the sensor, a classification-based algorithm via Pattern Recognition Method will be used to classify and match the food components. The results will displayed the total amount of calories consumed per day, per week and per month with total amount of calories left in a mobile application.